The Editor's Corner; Meet ACE Authors - R. E. Stevenson (Journal of Applied Communications, 1970)
Editorial back matter and the Editor's Corner for vol. 53, no. 2 (April-June 1970) of ACE, the official journal of the American Association of Agricultural College Editors